The Evolutionary Processes for the Populations of Firms and Workers - Accinelli Gamba, Elvio; Sánchez Carrera, Edgar J. (Universidad Autónoma de Nuevo León, 2010)
This paper analyzes the cultural evolution of firms and workers. Following an imitation rule, each firm and worker decides whether to be innovative (or not) and skilled (or unskilled). We apply evolutionary game theory to find the system of replicator dynamics, and characterize the low-level and highlevel equilibria as Evolutionarily Stable Strategies (ESS) “against the field.” Hence, we study how a persistent state of underdevelopment can arise in strategic environments in which players are imitative rather than rational maximizers. We show that when the current state of the economy is in the basin of attraction of the poverty trap, players should play against the field if they want to change their status quo. The threshold level to overcome the poverty trap can be lowered if there is an appropriate policy using income taxes, education costs and skill premia. Hence, we study the replicator dynamics with a subsidy and payoff taxation to overcome the poverty trap. JEL Classification: C72, C79, D83, O12.